Analysis of Environmental Accounting Reporting as Social Responsibility for Company Performance in Companies Listed on the Indonesia Stock Exchange - Intan Marsela; Mediaty Mediaty; Darwis Said (Department of Management FEB Unhas, 2020)
In an increasingly modern era, the industrial world continues to develop and increasingly complex. These developments have an impact on other elements around the industry, especially the environment. An increasingly advanced industry has an impact on the increasingly severe environmental damage due to waste pollution, mining, coal and others. The Indonesian Institute of Accountants has issued several SFAS related to environmental accounting. With the issuance of the PSAK the industrial world inevitably has to follow what has been regulated in the PSAK. SFAS related to environmental accounting is issued with the aim of ensuring that the company has carried out its obligations in the recovery of environmental damage caused by the company's operations.This research was conducted with the aim of ensuring that the company had followed the standards set by IAI in applying environmental accounting as one of its environmental responsibilities. This research was conducted using descriptive qualitative data. The results showed that the company in general had implemented PSAK especially number 57 related to the provision arising from company operations, the amount of the provision depends on the size of the company. With this research it is expected to be an alternative solution to the problem of environmental responsibility in order to add value to the company.Keywords: Environmental Accounting, Company Value, Statement of Financial Accounting Standards, Environmental Responsibility.